Effect of P-PST Program for Reinforcing Positives - Park, Sung-Joo; Jang, Kee-Duck (International Journal of Psychosocial Rehabilitation, 2020)
Background/Objectives: This study uses a problem-solving counseling program based on problem-solving counseling, which is one of the important theories of positive psychology, to promote adult’s positive thinking, positive emotion, positive attitude, and so on. It is meaningful to help solve various stresses and problems. Methods/Statistical analysis: Explain the purpose of this study for adults in G city from March 1 to 29, 2019, and select 20 volunteers, each week for 10 experimental groups and 10 control groups. The program was run on Saturday for eight weeks. The pre-test was conducted before the start of the program and the post-test after the post-test after the program was terminated. In order to verify the effect of the PST program for strengthening positiveness, covariate analysis was conducted using the pre-scores of positive thinking test, negative thinking test, positive emotion test and negative emotion test as covariates. Findings: As a result, it was found that the experimental group to which the PST program was applied had a statistically significant effect than the control group. In other words, it was proved that the experimental group treated with the PPST program was effective in improving positive thinking and positive emotions and reducing negative thinking and negative emotions. Improvements/Applications: The PPST program has been effective in reinforcing affirmations and can be used in a variety of programs. It is also effective in lowering individual’s negative viewpoints and raising positive aspects, which will be used to enhance life satisfaction and happiness.